Epidemiological study of myasthenia gravis in Japan. Issue 1 (9th December 2022) - Yoshikawa, Hiroaki
Abstract: Myasthenia gravis (MG) is an autoimmune‐mediated neurological disorder. The relationship between MG and thymic abnormalities is well recognized, and thymectomy is one of the therapies for anti‐acetylcholine receptor antibody‐positive MG. The major pathogenic factor is anti‐acetylcholine receptor antibody followed by anti‐muscle‐specific kinase antibody, and commercial kits are available to detect these antibodies. Several decades ago, the prognosis of MG was not favorable; therefore, the Ministry of Health and Welfare (predecessor of the Ministry of Health, Labor and Welfare) organized a Taskforce for Intractable Diseases, which included MG, in 1972. The Taskforce carried out consecutive epidemiological studies for MG in 1973, 1987, 2006 and 2018. The four studies found: (i) increasing prevalence; (ii) increasing late‐ and elderly‐onset; (iii) decreasing female dominancy; (iv) decreasing infantile‐onset (onset age of 0–4 years); and (v) decreasing frequencies of crisis. The latest epidemiological study in Japan and studies from other countries suggest an increasing number of patients with anti‐acetylcholine receptor antibody‐positive MG without thymoma in the elderly. It is important to find out the causes of this phenomenon, which will improve the prevention of MG.